The aggregate and country-specific effectiveness of ECB policy: Evidence from an external instruments (VAR) approach - Lucas Hafemann; Peter Tillman (Philipps-University Marburg, School of Business and Economics, 2017)
This paper studies the transmission of ECB monetary policy, both at the aggregate euro area and the country level. We estimate a VAR model for the euro area in which monetary policy shocks are identified using an external instrument that reflects policy surprises. For that purpose we use the change in German bunds at meeting days of the Governing Council. The identified monetary policy shock is then put into country-specific local projections in order to derive country-specific impulse responses. We find that (i) the trans- mission is very heterogeneous, both across channels and across countries, (ii) policy is transmitted through spreads, yields and the exchange rate, but less through banks and the stock market, and (iii) the strength of the transmission depends on structural characteristics of member countries, among them are current account balanced, debt to GDP levels, and the strength of banking systems.
Keywords: E52; E32; E44; 330; Euro area; VAR; external instrument; local projections; monetary transmission